Handbook on Social Protection Systems - Schüring, Esther; Loewe, Markus (Elgar Handbooks in Social Policy and Welfare, 2021)
This exciting and innovative Handbook provides readers with a comprehensive and globally relevant overview of the instruments, actors and design features of social protection systems, as well as their application and impacts in practice. It is the first book that centres around system building globally, a theme that has gained political importance yet has received relatively little attention in academia.